Workshop Rancang Bangun Jaringan Berbasis Kabel dan Nirkabel Dengan Vlan dan Routing Bagi Siswa SMK Muhammadiyah 1 Palembang - Yarza Aprizal; Andri Saputra; Yesi Sriyeni; Yuniansyah Yuniansyah (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
The workshop on cable-based and wireless networks with VLANs and routing using Mikrotik is one of the community service activities carried out by Lecturers at the Palembang Palembang Institute of Business Technology. The aim of this activity is to increase the skills of students at Muhammadiyah 1 Palembang Vocational High School. The activity will be carried out on Monday 8 January 2024. The implementation method uses lecture and practice methods. The training activity is divided into three parts, namely the first is a presentation about networks, VLANs and routing using a proxy, the second is practice in creating a network, VLAN configuration and routing using a proxy which is carried out alternately by the presenter and training participants and the third is an exercise as evaluation material to determine the participant's level of understanding. . The result of this activity is the increased ability of students at the Muhammadiyah 1 Palembang Vocational School Menangah regarding computer networks and VLANs. The implementation of this activity went well where the training participants were active and able to complete the exercises well and on time.